2006
DOI: 10.1007/s10562-006-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of atomized Ni3Al powder for hydrogen generation by methane steam reforming

Abstract: The catalytic activity of Ni 3 Al for methane steam reforming was investigated for the first time using its atomized powder. It was found that the activity was significantly enhanced by the combined pretreatment of acid and alkali leaching, while it was quite low for the as-received powder. The high activity was attributed to the formation of fine Ni particles on the porous surface of the powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
4
20
0
1
Order By: Relevance
“…The H 2 production rate of the pre-treated powder was above 90 ml min -1 g-cat -1 at 873 K, and showed no significant changes with the increase of reaction temperature. In contrast, the H 2 production rate of the as-received powder was nearly zero below 1123 K, and then increased markedly above 1123 K, which was consistent with our previous report [12]. These results show clearly that the oxidation-reduction pre-treatment significantly reduces the onset temperature of the catalytic 646 THERMEC 2009 Supplement activity to less than 873 K, i.e., the activity at lower temperatures is increased by the oxidation-reduction pre-treatment.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The H 2 production rate of the pre-treated powder was above 90 ml min -1 g-cat -1 at 873 K, and showed no significant changes with the increase of reaction temperature. In contrast, the H 2 production rate of the as-received powder was nearly zero below 1123 K, and then increased markedly above 1123 K, which was consistent with our previous report [12]. These results show clearly that the oxidation-reduction pre-treatment significantly reduces the onset temperature of the catalytic 646 THERMEC 2009 Supplement activity to less than 873 K, i.e., the activity at lower temperatures is increased by the oxidation-reduction pre-treatment.…”
Section: Resultssupporting
confidence: 93%
“…The as-received powder showed a rapidly solidified structure by the atomizing process (Fig. 4a), as we confirmed previously [12,13]. After oxidation at 973 K, an outer layer consisted of agglomerated granular particles was formed (Fig.…”
Section: Advanced Materials Research Vols 89-91 647supporting
confidence: 86%
See 2 more Smart Citations
“…We've recently developed their foils by cold rolling [2][3][4][5][6], which became possible using single crystalline ingots as a starting material [7]. Furthermore, we've found that they exhibit a catalytic activity for hydrogen production reactions such as methanol decomposition [8][9][10][11][12] and methane steam reforming [13,14]. Thus, the Ni 3 Al based foils can be used as a container and a catalyst in the micro chemical reactor for hydrogen production consequently.…”
Section: Introductionmentioning
confidence: 99%